Changes in the tension in dsDNA alter the conformation of RecA bound to dsDNA–RecA filaments - Conover, Alyson J. (Oxford University Press, 2011)
The RecA protein is an ATPase that mediates recombination via strand exchange. In strand exchange a single-stranded DNA (ssDNA) bound to RecA binding site I in a RecA/ssDNA filament pairs with one strand of a double-stranded DNA (dsDNA) and forms heteroduplex dsDNA in site I if homology is encountered. Long sequences are exchanged in a dynamic process in which initially unbound dsDNA binds to the leading end of a RecA/ssDNA filament, while heteroduplex dsDNA unbinds from the lagging end via ATP hydrolysis. ATP hydrolysis is required to convert the active RecA conformation, which cannot unbind, to the inactive conformation, which can unbind. If dsDNA extension due to RecA binding increases the dsDNA tension, then RecA unbinding must decrease tension. We show that in the presence of ATP hydrolysis decreases in tension induce decreases in length whereas in the absence of hydrolysis, changes in tension have no systematic effect. These results suggest that decreases in force enhance dissociation by promoting transitions from the active to the inactive RecA conformation. In contrast, increases in tension reduce dissociation. Thus, the changes in tension inherent to strand exchange may couple with ATP hydrolysis to increase the directionality and stringency of strand exchange.